2002
DOI: 10.1006/nbdi.2002.0539
|View full text |Cite
|
Sign up to set email alerts
|

Polyglutamine Repeat Length-Dependent Proteolysis of Huntingtin

Abstract: Amino-terminal fragments of huntingtin, which contain the expanded polyglutamine repeat, have been proposed to contribute to the pathology of Huntington's disease (HD). Data supporting this claim have been generated from patients with HD in which truncated amino-terminal fragments forming intranuclear inclusions have been observed, and from animal and cell-based models of HD where it has been demonstrated that truncated polyglutamine-containing fragments of htt are more toxic than fulllength huntingtin. We rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 39 publications
0
37
0
Order By: Relevance
“…The protease(s) involved remain to be determined. It could be a caspase cleaving at 214-EAND-217 (Berke et al, 2004) or, as reported for the cleavage fragment of other polyglutamine disease proteins, calpain or aspartic endopeptidases acting in concert with the proteasome (Kim et al, 2001;Gafni and Ellerby, 2002;Lunkes et al, 2002;Sun et al, 2002;Gafni et al, 2004). We expect that the mutant ataxin-3 fragment in our transgenic mouse brain will serve as a reference to identify a cell model and cellular components relevant to the appropriate processing of the disease protein.…”
Section: Mutant Ataxin-3 Putative-cleavage Fragmentmentioning
confidence: 85%
“…The protease(s) involved remain to be determined. It could be a caspase cleaving at 214-EAND-217 (Berke et al, 2004) or, as reported for the cleavage fragment of other polyglutamine disease proteins, calpain or aspartic endopeptidases acting in concert with the proteasome (Kim et al, 2001;Gafni and Ellerby, 2002;Lunkes et al, 2002;Sun et al, 2002;Gafni et al, 2004). We expect that the mutant ataxin-3 fragment in our transgenic mouse brain will serve as a reference to identify a cell model and cellular components relevant to the appropriate processing of the disease protein.…”
Section: Mutant Ataxin-3 Putative-cleavage Fragmentmentioning
confidence: 85%
“…The mechanisms of Htt induced toxicity are still largely unknown; however, there is mounting evidence that toxic poly(Q)-expanded Htt fragments are formed from fulllength Htt via proteolysis (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Thus, the Htt cleavage pathway and the molecules involved in it may represent potential therapeutic targets for intervention in HD.…”
Section: Huntington Disease (Hd)mentioning
confidence: 99%
“…6), an enzyme linked to a diverse array of pathologies. Calpain, like cathepsin D, is thought to produce aberrant fragments that assemble, or trigger the assembly of, aberrant intracellular structures such as the inclusions that characterize Huntington's Disease (Sun et al, 2002). The huntingtin protein fragments accumulate in the nucleus where they may gain access to the cell's transcription apparatus.…”
Section: Relationship Of Plasticity Deficits To Generalized Brain Agingmentioning
confidence: 99%